Surgical management of symptomatic osteonecrosis and utility of core decompression of the femoral head in young people with acute lymphoblastic leukaemia recruited into UKALL 2003. (1st March 2021) - Amin, Nadia; Kraft, Jeannette; Fishlock, Adelle; White, Alan; Holton, Colin; Kinsey, Sally; Feltbower, Richard; James, Beki
Abstract : Aims: Osteonecrosis (ON) can cause considerable morbidity in young people who undergo treatment for acute lymphoblastic leukaemia (ALL). The aims of this study were to determine the operations undertaken for ON in this population in the UK, along with the timing of these operations and any sequential procedures that are used in different joints. We also explored the outcomes of those patients treated by core decompression (CD), and compared this with conservative management, in both the pre- or post-collapse stages of ON. Methods: UK treatment centres were contacted to obtain details regarding surgical interventions and long-term outcomes for patients who were treated for ALL and who developed ON in UKALL 2003 (the national leukaemia study which recruited patients aged 1 to 24 years at diagnosis of ALL between 2003 and 2011). Imaging of patients with ON affecting the femoral head was requested and was used to score all lesions, with subsequent imaging used to determine the final grade. Kaplan-Meier failure time plots were used to compare the use of CD with non surgical management. Results: Detailed information was received for 85 patients who had developed ON during the course of their ALL treatment. A total of 206 joints were affected by ON. Of all joints affected by ON, 21% required arthroplasty, and 43% of all hips affected went on to be replaced. CD was performed in 30% of hips affected by ON. The majority of the hips were grade 4 or 5 at initial diagnosis of ON. There was no significant difference in time to joint collapse between those joints in which CD was performed, compared with no joint-preserving surgical intervention. Conclusion: There is a high incidence of surgery in young people who have received treatment for ALL and who have developed ON. Our results suggest that CD of the femoral head in this group of patients does not delay or improve the rates of femoral head survival. Cite this article: Bone Joint J  2021;103-B(3):589–596.